An atypical presentation of an extremely late stent thrombosis after more than 7 years (2634 days) of DES implantation in a patient without obvious risk factors on regular dual antiplatelet therapy. (15th July 2014) - Parekh, Pritesh; Agrawal, Navin; Vasavada, Apurva; Vinchurkar, Mahesh
Abstract : Very late stent thrombosis is a rare complication of percutaneous coronary intervention in the era of dual antiplatelet therapy. The risk factors for stent thrombosis are drug default, age, diabetes, renal dysfunction, left ventricular dysfunction, smoking or procedure-related factors and complications. We are describing the case of a 55-year-old non-smoker patient without the conventional risk factors for stent thrombosis maintaining good compliance with dual antiplatelet (aspirin and clopidogrel) drugs in standard doses. The patient had a history of having received a Cypher stent more than 7 years (2634 days) ago in the left circumflex artery for the management of in-stent restenosis of a bare metal stent implanted previously. He was referred with acute stent thrombosis with an atypical presentation of non-ST elevation myocardial infarction having unexplainable spontaneous resolution of electrocardiographic changes. The patient was successfully managed with newer generation drug-eluting stents reimplantation. The presence of acute onset of symptoms and thrombus containing soft lesion as documented during intervention supported the diagnosis of acute stent thrombosis. To the best of our knowledge this case is one of the longest duration of presentation with acute stent thrombosis after stent implantation ever reported in literature and is also unique in its unusual mode of presentation.